Middle managers' perception of the internal environment for corporate entrepreneurship: assessing a measurement scale - Hornsby, Jeffrey S; Kuratko, Donald F; Zahra, Shaker A (Journal of Business Venturing, 2002)
This study assesses the measurement properties of a scale that measures the key internal organizational factors that influence middle managers to initiate corporate entrepreneurship activities. In this study, corporate entrepreneurship is used in a broad sense to include the development and implementation of new ideas into the organization. Using this definition, this study describes an instrument used to empirically identify the internal conditions that influence middle manager's participation in corporate entrepreneurship activities. During the last decade, the role of the middle manager in corporate entrepreneurial activity has been recognized in the literature. The empirical research on the internal organizational factors that may foster middle manager activity has been limited, both in volume and scope. However, the literature does converge on at least five possible factors. The appropriate use of rewards: The literature stresses that an effective reward system that spurs entrepreneurial activity must consider goals, feedback, emphasis on individual responsibility, and results-based incentives. This factor, therefore, highlights middle managers' role in this regard. Gaining top management support: The willingness of senior management to facilitate and promote entrepreneurial activity in the organization, including championing innovative ideas as well as providing necessary resources, expertise or protection. This factor captures middle managers' role in this area. Resource availability: Middle managers must perceive the availability of resources for innovative activities to encourage experimentation and risk taking. Supportive organizational structure: The structure must foster the administrative mechanisms by which ideas are evaluated, chosen, and implemented. Structural boundaries tend to be a major stumbling block for middle management in corporate entrepreneurial activity. Risk taking and tolerance for failure: Middle managers must perceive an environment that encourages calculated risk taking while maintaining reasonable tolerance for failure. The literature on the internal factors was utilized to develop an assessment instrument called the Corporate Entrepreneurship Assessment Instrument (CEAI). The instrument contained 84 Likert-style questions that were believed to assess a firm's internal entrepreneurial environment. Understanding middle manager perceptions about the internal corporate environment is crucial to initiating and nurturing any entrepreneurial process. A scale such as the CEAI, therefore, could be very useful for companies that wish to embark on a strategic transformation through corporate entrepreneurship. The measurement properties of the CEAI, including a factor analysis and reliability assessment, were determined. Results confirmed that five distinct internal organizational factors, similar to those suggested in the literature, do exist. Based on how the items loaded on each factor, the factors were entitled management support, work discretion, organizational boundaries, rewards/reinforcement, and time availability. The reliability of each of these factors also met acceptable measurement standards. From a managerial perspective, the results indicate that CEAI can be a useful tool in diagnosing a firm's environment for corporate entrepreneurship, identifying areas where middle managers can make a significant difference, and develop strategies that can positively spur and sustain corporate entrepreneurship efforts. The results of such diagnosis can be useful in designing effective training programs for middle managers.